A field study on indoor environmental quality and energy savings of an office building integrated with underfloor air conditioning system in India. (7th February 2023) - Lakshmanan, Ramesh Krishnan; Lachireddi, Gangadhara Kiran Kumar
Abstract : This study aimed to examine the real-time indoor environmental quality (IEQ) factors in an office space environment with a dedicated underfloor air conditioning system. Nevertheless, underfloor air distribution (UFAD) system buildings in India do not have reliable studies to record the impact of occupant perception and IEQ factors. This study was conducted in the UFAD office building during the peak monsoon period of 16 th – 25 th October 2019 in a warm and humid climate region of Mumbai, India. IEQ factors of indoor thermal, air quality, lighting, and noise comfort were examined using an occupant questionnaire survey for sensation, preference and overall acceptability, as well as physical measurements. Furthermore, energy consumption and energy utilization coefficient were determined at different room set-point temperatures. Four hundred and thirty-five responses were collected during the field study. The comfort zone temperature was obtained between 22.24–25.3 °C with near-zero (±0.5) tolerance range. Moreover, 80-95% of the occupants felt comfortable and acceptable within the thermal environment of the room set-point at 22-25 °C. Results showed that the real-time IEQ score was perceived between 0.663-0.846. The real-time IEQ score can be used as a building management strategy that simultaneously improves thermal comfort and indoor air quality.